2000
DOI: 10.1046/j.1365-2702.2000.00394.x
|View full text |Cite
|
Sign up to set email alerts
|

Education and training towards competency for cardiac rehabilitation nurses in the United Kingdom

Abstract: The development of cardiac rehabilitation in the UK, the evolution of the nursing role as a speciality, and the nursing role within the multidisciplinary team are briefly outlined. The potential impact of different professional backgrounds on the effectiveness of patient care is discussed, with particular reference to the differences between acute cardiac care and rehabilitation. Issues of professional competency are discussed, and core competencies for cardiac rehabilitation as specified by various profession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…185 A coherent approach to the education of programme coordinators and staff on the benefits of cardiac rehabilitation and its application in patient groups may lead to better understanding of patient eligibility and thus wider invitation. 193 Appointment of a programme director to lead, audit and commission appropriate resources for cardiac rehabilitation may lead to improvements in service management and provision. 32 This may facilitate the running of programmes in accordance with national guidelines, which may help to improve provision.…”
Section: Discussionmentioning
confidence: 99%
“…185 A coherent approach to the education of programme coordinators and staff on the benefits of cardiac rehabilitation and its application in patient groups may lead to better understanding of patient eligibility and thus wider invitation. 193 Appointment of a programme director to lead, audit and commission appropriate resources for cardiac rehabilitation may lead to improvements in service management and provision. 32 This may facilitate the running of programmes in accordance with national guidelines, which may help to improve provision.…”
Section: Discussionmentioning
confidence: 99%
“…It was surprising that systematic review identified so few trials, as the literature contains many suggested interventions as facilitators of improved uptake, adherence and professional compliance in cardiac rehabilitation. Uptake of services is influenced by the knowledge and enthusiasm of physicians, other care providers and rehabilitation professionals (Young & Kahana 1989, King & Teo 1998, Stokes 2000, and education on the benefits of cardiac rehabilitation and its application could improve referral and uptake (Bittner et al 1999). Greater involvement of referring physicians in the programme may be required (Comoss 1988), and Integrative literature reviews and meta-analyses Improving uptake and adherence in cardiac rehabilitation Comoss (1988), Emery (1995) Provide classes at convenient times including before work and evenings Reviews Oldridge (1984) Varied programme: swimming; exercise equipment Review Knapp and Blackwell (1985) Offering specific and practical assistance for spouses (e.g.…”
Section: Improving Uptake and Adherencementioning
confidence: 99%
“…In the UK, attaining agreed national standards and competencies is crucial for meeting the needs of patients and nurses while enabling workforce and service planning for the National Health Service . It is recognised that an education and training programme can help nurses to attain competencies and meet standards …”
Section: Introductionmentioning
confidence: 99%
“…1,3,4 It is recognised that an education and training programme can help nurses to attain competencies and meet standards. 1,5 Congenital cardiac care is increasingly being delivered using a network model in the UK, with the main surgical centre leading and coordinating care across the network with the aim of enabling patients to receive elements of care closer to home. 1 There are a variety of standardised nursing roles across the cardiac network 1,3,4 and the education and training needs of nurses within these roles vary considerably.…”
mentioning
confidence: 99%